An atomic-level insight into the basic mechanism responsible for the enhancement of the catalytic oxidation of carbon monoxide on a Cu/CeO2 surface. Issue 5 (30th November 2016) - Koizumi, Kenichi; Nobusada, Katsuyuki; Boero, Mauro
Abstract : Reaction mechanism of CO molecules onto a Cu/CeO2 surface and morphological changes. Abstract : The reaction mechanisms of CO molecules interacting with a Cu/CeO2 surface and related morphological modifications occurring upon removal of O atoms to generate CO2 are investigated by first-principles dynamical simulations complemented by a free-energy sampling technique. We show that the reactivity of oxygen atoms located in the first layer in the vicinity of the Cu site is remarkably high because of a reduction of the O coordination number. Moreover, we evidence that the doped Cu atoms are responsible for an enhancement of the exposure of other surrounding O atoms, even below the first surface layer, which can then easily react with CO and are gradually removed from the system in the oxidation process. The underlying mechanism responsible for such a high catalytic reactivity of the Cu/CeO2 surface toward CO oxidation is rationalized in terms of the characteristics of the doped Cu. In fact, this copper site is responsible for providing an increasing number of O atoms participating in the catalysis by exposing subsequently all O atoms in the vicinity which are likely to react with an approaching CO. This peculiarity of the Cu atoms extends to O atoms which initially can be deeply buried up to the fourth layer underneath the surface. The mechanism unveiled here provides useful insights into the fundamental mechanism and suggests strategies for the engineering and design of more effective ceria-based catalysts via metal doping.